Educational needs in palliative care of Primary Health Care nurses - Spineli,Vívian Marina Calixto Damasceno (2022)
ABSTRACT Objectives: to understand the experience of Primary Health Care nurses with palliative care and their educational needs on the topic. Methods: an exploratory study, with a qualitative approach. The data was collected through 19 focus groups involving 181 nurses. In interpreting the results, the thematic analysis was used. Results: the knowledge presented by nurses in palliative care proved to be limited. Gaps were identified in the definition of palliative care and in the philosophical principles that guide it. The experiences described highlighted the need for continuing education regarding the definition and philosophy of palliative care, patient eligibility, integral care to the patient and the family, interpersonal communication and difficult news, performance in a multi-professional team, and end-of-life care. Final Considerations: the analysis of the perceptions of Primary Health Care nurses about palliative care can help identify the obstacles to improving the provision of this care modality.